2000
DOI: 10.1378/chest.117.4.976
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effects of Outpatient Rehabilitation of COPD

Abstract: Outpatient rehabilitation programs can achieve worthwhile benefits that persist for a period of 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
176
1
11

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(203 citation statements)
references
References 25 publications
(19 reference statements)
9
176
1
11
Order By: Relevance
“…Long-term maintenance of any increase is challenging. Strategies such as regular telephone support and follow-up visits may be insufficient [61]. It is likely that sustained gains in physical activity and/or reductions in sedentary behaviour in this population will require complex interventions that may include exercise training, goal setting and motivational interviewing.…”
Section: Increasing Physical Activitymentioning
confidence: 99%
“…Long-term maintenance of any increase is challenging. Strategies such as regular telephone support and follow-up visits may be insufficient [61]. It is likely that sustained gains in physical activity and/or reductions in sedentary behaviour in this population will require complex interventions that may include exercise training, goal setting and motivational interviewing.…”
Section: Increasing Physical Activitymentioning
confidence: 99%
“…Furthermore, there is a need to understand better what patients perceive as an 'exacerbation. ' Studies vary in their definitions of COPD 'exacerbations' [4][5][6][7][8][9][10][11][12][13][14][15], thus making evaluation and comparison difficult, a problem identified in the GOLD international guidelines for the management of COPD. Indeed, the authors of the GOLD guidelines use the term 'exacerbation' without a clear definition [16].…”
Section: Introductionmentioning
confidence: 99%
“…This diminution of benefit has been reported in several programs (4)(5)(6)11). Longer programs may well extend the duration of improvement (13)(14)(15). Troosters et al (16) reported on 100 patients randomly assigned to a six-month program of rehabilitation.…”
Section: Diminution Of Benefits With Timementioning
confidence: 88%